2022
DOI: 10.1002/ldr.4518
|View full text |Cite
|
Sign up to set email alerts
|

Plant types shape soil microbial composition, diversity, function, and co‐occurrence patterns in cultivated land of a karst area

Abstract: Plants can alter microbial communities through root exudates, and change the characteristics of the soil. However, the relationship between soil microbial communities and environmental factors is not well understood. Here, we studied bacterial and fungal communities and their relationships with environmental factors. We integrated data of environmental factors, microbial composition, diversity, functional prediction, and co-occurrence network from uncultivated, maize, cabbage, and cocozelle soils in a karst ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 87 publications
4
7
0
Order By: Relevance
“…cross‐feeding, syntrophic interactions, and commensalism as well as shared habitat requirements) dominated the ecological network. Similar, Wei et al (2023) in a karst region of Southwest China and Chen et al (2023) in the Inner Mongolia Plateau also found that the ratio of positive to negative edges increased when the soil environmental conditions became better and stable. The increasing in cooperative and co‐dependence relationships among soil microorganisms was conducive to better use of environmental resources for microorganism's growth in suitable habitats, and thus increasing the ratio of positive to negative edges in ecological network of soil microbial community in these studies (Chen et al, 2023; Li et al, 2023).…”
Section: Discussionsupporting
confidence: 63%
“…cross‐feeding, syntrophic interactions, and commensalism as well as shared habitat requirements) dominated the ecological network. Similar, Wei et al (2023) in a karst region of Southwest China and Chen et al (2023) in the Inner Mongolia Plateau also found that the ratio of positive to negative edges increased when the soil environmental conditions became better and stable. The increasing in cooperative and co‐dependence relationships among soil microorganisms was conducive to better use of environmental resources for microorganism's growth in suitable habitats, and thus increasing the ratio of positive to negative edges in ecological network of soil microbial community in these studies (Chen et al, 2023; Li et al, 2023).…”
Section: Discussionsupporting
confidence: 63%
“…The observed inverse relationship between pH levels and total nitrogen (TN) content, as well as microbial communities, aligns with previous investigations [ 66 , 67 ]. Consequently, the makeup of soil microbial communities is impacted [ 68 ], thereby highlighting the significance of organic matter as a key determinant of fungal communities [ 69 ]. The findings of AN and AP in a study conducted by Sun et al [ 70 ] exhibited a resemblance to the results observed in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, all co-occurrence topological features were calculated, and the network image was generated with the "igraph" package in R (Wei et al, 2023). Detailed steps of co-occurrence network construction are provided in the Supporting Information.…”
Section: Discussionmentioning
confidence: 99%
“…Then, using the “sciplot” and “ggmisc” packages, we analyzed the significantly different modules in the bacterial co‐occurrence network and correlations between the significantly different modules and SOC storage (Hartman et al, 2018). Finally, all co‐occurrence topological features were calculated, and the network image was generated with the “igraph” package in R (Wei et al, 2023). Detailed steps of co‐occurrence network construction are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%